Visual styles, hidden discourses: An exploratory case study of a Chilean education university - Bravo, Úrsula; Marini, Guillermo (FormAkademisk, 2023)
This article reports the findings of a study aimed at exploring the visual discourses at a Chilean education university. First, building on the classic ‘hidden curriculum’ and ‘school art style’ literature, it justifies the need to discuss how higher education institutions model the ways through which teachers-to-be comprehend and use visual resources. Second, the article presents the results of a critical visual methodology performed in the oldest education university in Chile. Through a visual discourse analysis of the experience of walking around the campus, it elaborates on the university’s visual styles comprising the themes, technologies and locations of artefacts. Third, it discusses the relationships between courtyard and hallway images loaded with critical motivations and classroom images portraying stereotyped and anachronistic views of childhood. The article concludes by urging to incorporate quality visual pedagogy orientations in teacher education.